The Role of Real-Time Learning Analytics and Pedagogical Chatbots in Improving Digital Literacy and Self-Regulated Learning among Islamic Senior High School Students - Suardi, Suardi (Asian Journal of Applied Education (AJAE), 2025)
This study examines the impact of integrating real-time learning analytics and pedagogical chatbots on enhancing digital literacy and self-regulated learning among Madrasah Aliyah students. Using a mixed-methods approach with a pre-test–post-test quasi-experimental design involving 120 students, quantitative data were collected through digital literacy tests, self-regulated learning scales, and activity logs, while qualitative data came from semi-structured interviews. Results showed a significant improvement in both digital literacy and self-regulated learning in the experimental group compared to the control group, with a positive correlation between chatbot interaction intensity and learning outcomes. Qualitative findings revealed that real-time feedback and adaptive chatbot guidance enhanced students’ intrinsic motivation and learning management skills. Overall, the integration of these technologies effectively strengthens 21st-century competencies and offers strategic implications for technology-based learning design in Islamic senior high schools.